Lecanemab (Leqembi) - CDA-AMC (Canadian Journal of Health Technologies, 2026)
Canada’s Drug Agency (CDA-AMC) recommends that Leqembi be reimbursed by public drug plans for the treatment of adult patients in the early stages of Alzheimer disease (AD) (i.e., mild cognitive impairment [MCI] or mild dementia) who have evidence of amyloid in the brain and who are APOE epsilon 4 (APOE4) noncarriers or heterozygotes, if certain conditions are met. Leqembi should only be covered to treat adult patients aged 50 years or older who have a clinical diagnosis of early AD with confirmed amyloid pathology using a validated method, and who are APOE4 noncarriers or heterozygotes. Leqembi should only be reimbursed if prescribed by clinicians with expertise and experience in the diagnosis, management, and treatment of AD, in a setting with timely access to MRI. Treatment should not be initiated, and should be discontinued, in patients who are unable or unwilling to undergo the recommended MRI monitoring for amyloid-related imaging abnormalities (ARIAs). Leqembi should only be used in patients without symptomatic ARIAs or moderate to severe radiographic ARIAs, and if the cost of Leqembi is reduced. Leqembi should not be reimbursed in combination with other monoclonal antibody therapies for AD or upon disease progression to moderate dementia.